Does impaired grammatical comprehension provide evidence for an innate grammar module? - Courtenay Frazier Norbury; Dorothy V. M. Bishop; Josie Briscoe (2002)
Children with specific language impairment (SLI) have distinctive impairments in the comprehension of sentences that involve long-distance syntactic relationships. This has been interpreted as evidence for impairment in an innate grammatical module. An alternative theory attributes such difficulties to lower level problems with speech perception or deficits in phonological working memory. These theoretical accounts were contrasted using comprehension data from three subgroups: 20 children with SLI, 19 children with mildmoderate hearing loss, and normally developing children matched on age and/or language level. There were close similarities between the hearing-impaired and SLI groups on a measure of phoneme perception. Children with SLI did poorly on tests assessing knowledge of Binding principles and in assigning thematic roles in passive sentences whereas hearing-impaired children performed close to control levels, indicating that poor speech perception cannot account for this pattern of deficit. However, the pattern of errors on syntactic tasks and the relatively weak correlation between different indicators of syntactic deficit seemed incompatible with a modular hypothesis. We propose that limited processing capacity is the principal determinant of deficient syntactic comprehension in SLI.